Development of Analytical Conditions for the Isolation of Ketamine from Urine by High-Performance Liquid Chromatography Method (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
This article presents the results of the development of methods for extracting ketamine from the biological fluid urine and determining its amount using the method of high-performance liquid chromatography. The linearity and accuracy of the analysis method were studied. The possibility of detection and quantitative analysis of norketamine in extracts extracted from biological fluid using this method has been shown. In the practice of forensic chemistry, it is recommended to use the methods of chemical-toxicological analysis developed in cases of poisoning with ketamine.